Marmota caligata - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Marmota caligata (Eschscholtz, 1829). Zool. Atlas, Part 2, p. 1, pl. 6. TYPE LOCALITY: U.S.A., Alaska, near Bristol Bay. DISTRIBUTION: C. Alaska (U.S.A.), Yukon and Northwest Territories (Canada) south to W. and N.E. Washington, C. Idaho, and W. Montana (U.S.A.). ISIS NUMBER: 5301410002016002001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 1), pp. 345-382 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 355, DOI: 10.5281/zenodo.7353023